2021
DOI: 10.52547/jcc.3.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mg and MgO Nanoparticles on Microstructural and Mechanical Properties of Aluminum Matrix Composite Prepared via Mechanical Alloying

Abstract: Aluminum-based composites reinforced with ceramic particles have been used for many applications because of their high hardness, good wear resistance, low weight, and low thermal expansion coefficient. The Al-MgO/Mg composite was prepared in the present study. The effects of milling time and amounts of initial Mg and MgO were studied on the properties of the composite. The milled powder mixtures were subsequently analyzed by the XRD and SEM tests. Crystal sizes and internal strains were calculated using XRD da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It has also been reported that the presence of pectin can regulate the particle size and morphology of HA [45], ensuring good cell adhesion for various types of bone cells [46]. Furthermore, ball milling can achieve high density by completing surface activation of silica powder [47] and obtain uniform distribution of Mg and MgO nanoparticles in an aluminum matrix [48]. Therefore, it is believed that ball milling will help improve the densification of HA in this research.…”
Section: Introductionmentioning
confidence: 79%
“…It has also been reported that the presence of pectin can regulate the particle size and morphology of HA [45], ensuring good cell adhesion for various types of bone cells [46]. Furthermore, ball milling can achieve high density by completing surface activation of silica powder [47] and obtain uniform distribution of Mg and MgO nanoparticles in an aluminum matrix [48]. Therefore, it is believed that ball milling will help improve the densification of HA in this research.…”
Section: Introductionmentioning
confidence: 79%
“…Because of their excellent characteristics, such as biocompatibility, good catalytic properties, high electrical conductivity, and facilitation of electron transfer between electrodes and biomolecules, typical noble-metal nanoparticles (Au, Ag, Pt, etc) are widely used in biomolecule sensing and DNA hybridization [59,60]. AuNPs can provide a suitable microenvironment for the immobilization of biomolecules while keeping their biological activity and facilitating electron transport between electrode surfaces and immobilized proteins, resulting in their widespread application in biosensors [61].…”
Section: Metal Nanoparticle-based Biosensorsmentioning
confidence: 99%